Meningkatkan Kemampuan Motorik Halus Anak Melalui Permainan Paper Cup Pada Usia 4-5 Tahun Di TK Qurrota A’yun 01 Aisyiyah Kota Pekalongan Tahun Ajaran 2020/2021 - Rusdianah Rusdianah (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
This study aims to improve the fine motor skills of children in QURROTA A'YUN 01 AISYIYAH KOTA PEKALONGAN at the age of 4-5 years. This study uses classroom action research (CAR). The research subjects at QURROTA A'YUN 01 AISYIYAH TK, PEKALONGAN CITY, group A consisted of 16 children, 8 boys and 8 girls. Data collection techniques through observation and documentation. The results showed an increase in children's fine motor skills through the use of the "Paper Cup" media, namely in the pre- cycle 31.25% of 16 children, the improvement of fine motor skills in the first cycle of 50% of 16 children and in the second cycle of 82.5% of the second meeting. The conclusion of this research is that using the paper Cup media can improve fine motor skills and think about how to carry out activities with the Coffee Cup game.